Analisis Keseimbangan Lintasan Produksi dalam Upaya Mengurangi Waktu Tunggu pada Proses Produksi Kursi (Studi Kasus: UD. XYZ) - Alfiono, Bima; Mundari, Siti (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
UD. Santoso Mandiri is a company engaged in the furniture industry and applies a make-to-order system in producing chairs. The company faces an imbalance in the production line, particularly at the bending and welding stations, which leads to work accumulation. This study aims to minimize delays at workstations to achieve a balanced production line. Data were collected through observation and interviews, then analyzed using the Ranked Positional Weight and Region Approach methods. The results showed that the Ranked Positional Weight method provided more optimal outcomes, with a proposed reduction in the number of workstations from five to three. The grouping of work elements was carried out based on priority order and completion time. As a result, line efficiency increased to 72.95%, while balance delay decreased to 27.05%. This study is expected to help create a more balanced workflow and reduce delays in the production process.